2019
DOI: 10.1088/1742-6596/1272/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Heath-Carter somatotype in adults using bioelectrical impedance analysis

Abstract: Using cross-sectional anthropometric data of 897 ethnically Russian individuals aged 16-61 years from the European part of Russia (Arkhangelsk, Moscow, and Samara), we checked the accuracy of our previously proposed bioimpedance-based formulae for the assessment of the endomorphy and mesomorphy ratings of the Heath-Carter somatotype, and suggested the revised formulae: ENDOBIA= -3,399/R + 0.992×BMI - 0.0102×BMI 2 -0.85×Sex - 5.93 (r 2=0.80; SEE=0.91); MESOBIA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…Similar formulae were suggested for adults [ 61 , 62 ]. As a result, it became possible to utilize regular BIA data (including that of mass population studies) for a reliable assessment of the somatotype and, hence, the Heath-Carter somatotyping has become much more accessible.…”
Section: Main Textsupporting
confidence: 60%
“…Similar formulae were suggested for adults [ 61 , 62 ]. As a result, it became possible to utilize regular BIA data (including that of mass population studies) for a reliable assessment of the somatotype and, hence, the Heath-Carter somatotyping has become much more accessible.…”
Section: Main Textsupporting
confidence: 60%
“…1), на которые были нанесены восемь уровней согласно методу унифицированного обозначения чрескостного остеосинтеза (МУОЧО) [10]. Компоновки были исследованы на трех типах моделей нижних конечностей, имитирующих эктоморфный, мезоморфный, эндоморфный соматотипы, определяемые по методу B. Heath, J. Cartner [11][12][13]. Для моделирования конечностей были проведены замеры длины бедра и голени и их окружности на трех уровнях у 27 пациентов, относящихся к эктоморфному, у 30 пациентов, относящихся к мезоморфному, и у 29 пациентов, относящихся к эндоморфному соматотипу (рис.…”
Section: материал и методы исследованияunclassified
“…Taking into account the age of our group, we could use only two existing BIA-based formulas [17,23] for endo-and mesomorphy. The statistical results obtained (Table A1) by using equations to assess endo-and mesomorphy in age groups 16-61 and 16-40, indicate how limited those applications are in our group.…”
Section: Weights and Biasesmentioning
confidence: 99%
“…It was shown that inter-and intra-individual variability in the selection of skinfold sites, depth and time delay in reading the calipers reduce the accuracy of this procedure and remain a major source of error associated with this technique [15,16]. Moreover, the disadvantages of anthropometric measurements limit the availability of large-scale research [17]. Measurements should be made in several repetitions by 2 researchers, can be tiring and depressing for the participant and can be negatively perceived as interference with the physical space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation